Cancer: New Needs, New Models. Is It Time for a Community Oncologist? Another Brick in the Wall - Tralongo, Paolo (Cancers (Basel), 2021)
SIMPLE SUMMARY: Community care activity in the oncology field does not exist. This unmet need contrasts with the increasing number of patients with a previous diagnosis of cancer. ABSTRACT: Over the last few decades, thanks to early detection, effective drugs, and personalized treatments, the natural history of cancer has radically changed. Thanks to these advances, we have observed how survival of cancer patients has increased, becoming an ever more important goal in cancer care. Effective clinical governance of survivorship care is essential to ensure a successful transition between active and post-treatment life, identifying optimization of healthcare outcomes and quality of life for patients as the primary objectives. For these reasons, potential intervention models must consider these differences to rationalize the available resources, including economic aspects. In this perspective, analyzing the different models proposed in the literature to manage this type of patients, we focus on the possible role of the so-called “community oncologist”. As a trained health professional, also focused on longevity, he could represent the right management solution in all those “intermediate” clinical conditions that arise between the hospital specialist, frequently overworked, and the general practitioner, often biased by the lack of specific expertise.